Micro- and Macro-Anatomical Frameworks of Lymph Nodes Indispensable for the Lymphatic System Filtering Function - Ozawa, Madoka; Nakajima, Shihori; Kobayashi, Daichi; Tomii, Koichi; Li, Nan-Jun; Watarai, Tomoya; Suzuki, Ryo; Watanabe, Satoshi; Kanda, Yasuhiro; Takeuchi, Arata; Katakai, Tomoya (Frontiers in Cell and Developmental Biology, 2022)
In the lymphatic vascular system, lymph nodes (LNs) play a pivotal role in filtering and removing lymph-borne substances. The filtering function of LNs involves resident macrophages tightly associated with unique lymphatic sinus structures. Moreover, an intermittently arranged LN in the lymphatic pathway is considered to cooperatively prevent lymph-borne substances from entering blood circulation. However, the functional significance of tissue microarchitecture, cellular composition, and individual LNs in the “LN chain” system is not fully understood. To explore the mechanistic and histo-anatomical significance of LNs as lymph fluid filters, we subcutaneously injected fluorescent tracers into mice and examined the details of lymphatic transport to the LNs qualitatively and quantitatively. Lymph-borne tracers were selectively accumulated in the MARCO+ subcapsular-medullary sinus border (SMB) region of the LN, in which reticular lymphatic endothelial cells and CD169+F4/80+ medullary sinus macrophages construct a dense meshwork of the physical barrier, forming the main body to capture the tracers. We also demonstrated stepwise filtration via the LN chain in the lymphatic basin, which prevented tracer leakage into the blood. Furthermore, inflammatory responses that induce the remodeling of LN tissue as well as the lymphatic pathway reinforce the overall filtering capacity of the lymphatic basin. Taken together, specialized tissue infrastructure in the LNs and their systematic orchestration constitute an integrated filtering system for lymphatic recirculation.